Efficacy of Yogic Practices on Physical Skills of Badminton Players at College Level: The impact of yogic practices on physical skills and wellness of college level badminton players (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The goal of the examination is to research the effect of yogic practice on chosen physical and physiological variables among badminton players. Yoga is the craftsmanship and exploration of keeping up physical and mental prosperity that has its beginning in India, which is among the most antiquated at this point energetic living customs that are getting progressively prevalent today. The requirement for yoga in the present time is to fabricate a healthy and mentally ready native, a solid nation by creating general wellness of residents with yoga activities like yogic asana. There are such huge numbers of concentrates accessible with respect to the impact of exercises on different segments of motor abilities of an ordinary individual.